2012
DOI: 10.1002/jbm.a.34281
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of protein microfiber networks supporting pancreatic islets

Abstract: Networks of discrete, genipin-crosslinked gelatin microfibers enveloping pancreatic islets were incorporated within barium alginate microcapsules. This novel technique enabled encapsulation of cellular aggregates in a spherical fibrous matrix <300 μm in diameter. Microfibers were produced by vortex-drawn extrusion within an alginate support matrix. Optimization culminated in a hydrated fiber diameter of 22.3 ± 0.4 μm, a significant reduction relative to that available through current gelatin microfiber spinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Microfluidic fibers can be formed with various polymers, including gelatin-hydroxyphenylpropionic acid, alginate, chitosan, gelatin, and poly (lactic-co-glycolic acid) (PLGA). Microfluidic spinning is the proper technology for cell encapsulation because the fibers can be continuously produced and cover the cells without the need for a high voltage or temperature [63]. In microfluidics, PDMS-based and glass-based microfluidic chips are mainly used.…”
Section: Msc Encapsulation Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Microfluidic fibers can be formed with various polymers, including gelatin-hydroxyphenylpropionic acid, alginate, chitosan, gelatin, and poly (lactic-co-glycolic acid) (PLGA). Microfluidic spinning is the proper technology for cell encapsulation because the fibers can be continuously produced and cover the cells without the need for a high voltage or temperature [63]. In microfluidics, PDMS-based and glass-based microfluidic chips are mainly used.…”
Section: Msc Encapsulation Technologymentioning
confidence: 99%
“…In microfluidics, PDMS-based and glass-based microfluidic chips are mainly used. These types of devices are easily extruded using similar materials and methods [63, 64]. Liu et al reported mouse BMSC encapsulated alginate microfibers using microfluidic technology for vascular grafts [65].…”
Section: Msc Encapsulation Technologymentioning
confidence: 99%
“…3742 Gelatin is the denaturized form of collagen but differs in some important characteristics such as gelation time and the presentation of binding site sequences. 43…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40][41][42] Gelatin is the denaturized form of collagen but differs in some important characteristics such as gelation time and the presentation of binding site sequences. 43 Synthetic scaffold materials. The most frequently used synthetic material investigated in the reviewed studies was PEG and its derivatives poly(ethylene glycol) diacrylate (PEGDA) and poly(ethylene glycol) dimethacrylate (PEGDM) (n = 53 in total).…”
Section: Scaffold Materialsmentioning
confidence: 99%
“…Various imaging markers have been co-encapsulated with islets, such as SPIOs integrated with near-infrared fl uorescent Cy5.5 dye for 1 H MRI and optical imaging [ 44 ] , perfl uorocarbons for 19 F MRI, ultrasound, and CT [ 60 ] , and gold nanoparticles coated with Gd chelates for 1 H MRI, CT and ultrasound [ 61 ] . The inside of the capsule can also be modifi ed into a protein microfi ber network to better support the embedded islets [ 62 ] . Moreover, Kim et al developed "capsule-in-capsules" containing gold and iron nanoparticles for MRI, CT and ultrasound [ 63 ] , in which the islets were not only separated from the immune system but also from the nanoparticles to prevent potential toxic eff ects of the iron.…”
mentioning
confidence: 99%